Prospects for the development of Tourism - Javlieva Feruza Mirzamurodovna (Periodica Journal, 2025)
The development of the tourism sector is today an important factor not only in the economic growth of countries, but also in the strengthening of cultural exchange and international cooperation. Uzbekistan's geographical location, rich historical heritage and cultural diversity make it an attractive destination for tourism. The prospects for the development of tourism can serve to diversify the country's economy, create new jobs and increase the well-being of local residents.
Keywords: Tourism; Investment; Society